PHYSICAL EVALUATION FOR SCHOOL CHILDREN (Fiep Bulletin - online, 2014)
Physical activity is very important on any age and earlier initiated, more benefits must provide to the individual. In this sense, it is fundamental to stimulate the child to participate of Physical Education classes as soon as possible. However, to obtain good results it is necessary that the physical activity to be practiced under professional supervision, respecting the development of the children. One way of assisting the professor to follow the evolution of his/her students and also to make a self-evaluation of his/her class programme is by means of the periodic accomplishment of evaluation tests. The presented work is focused on this subject, aiming at to select a subset of evaluation tests which allows evaluating students during physical educational classes. The idea is that, by evaluating such students with the considered tests, it is possible the teacher to use the collected data to identify problems, such as the childhood overweight, and also to check whether the benefits of his/her classes are being reached. Since the collection, storage and analysis of the test data is a cumbersome activity, different mechanisms have being proposed to help the teacher to accomplish the evaluation tests. We are working on the development of a computer programme, called "Medida-Certa" which eases the collection and storage of evaluation test data, and also provides a set of reports to help the teacher to analyze the results of the tests from different perspectives. An example of using such a program is also presented and compared with other alternatives.
Keywords: Tests; Evaluation; School Children